Local Pride Movement As A Local Sneaker Branding Strategy - Suseno, Bayu Aji; Hidayat, Anwar (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2021)
This research aims to determine the revival of local pride tagline or slogan as a social movement for being proud of wearing local sneaker brand. In this research, the branding theory was used to analyze the formation of local pride or being pride of Indonesian-made products slogan or taglines. This research used a qualitative method with an analytic descriptive approach. Meanwhile, data were collected through non-participant observation to obtain an overview or information about objective or event conditions. The research result showed that the local pride movement practiced through cross-industry collaboration with influencers was able to build the brand personality of local shoes on consumers’ buying interests. The level of consumer ethnocentrism in the community resulted in brand awareness providing significant effects on the decision to buy local shoes. It was also in line with the government policy through restriction on imported commodities for products or goods that can be made domestically. The Content digital marketing was adopted by developing a proud Indonesian products theme. It was carried out through a hashtag for #LocalPride to increase the number of local shoes product sales, and it also can be used as a promotional tool that has proven to be effective to increase the number of followers on social media.